2020
DOI: 10.3389/fphar.2020.00757
|View full text |Cite
|
Sign up to set email alerts
|

The Bone Extracellular Matrix in Bone Formation and Regeneration

Abstract: Bone regeneration repairs bone tissue lost due to trauma, fractures, and tumors, or absent due to congenital disorders. The extracellular matrix (ECM) is an intricate dynamic bio-environment with precisely regulated mechanical and biochemical properties. In bone, ECMs are involved in regulating cell adhesion, proliferation, and responses to growth factors, differentiation, and ultimately, the functional characteristics of the mature bone. Bone ECM can induce the production of new bone by osteoblast-lineage cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
316
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 423 publications
(394 citation statements)
references
References 120 publications
6
316
0
Order By: Relevance
“…In addition, 45-nm AuNPs promoted greater expression of bone-specific matrix proteins (OPG, OPN, and OCN) ( Figure 6), which were highly expressed by osteoblasts and osteocytes. 37 All these results indicated that AuNPs, especially 45-nm AuNPs, could enhance osteogenic differentiation and matrix mineralization. However, it cannot be denied that there are differences between ectopic and orthotopic models, and further well-designed experiments in alveolar bone-defect models are needed to verify the osteogenic effects of AuNPs on PDLSC sheets.…”
Section: Dovepressmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, 45-nm AuNPs promoted greater expression of bone-specific matrix proteins (OPG, OPN, and OCN) ( Figure 6), which were highly expressed by osteoblasts and osteocytes. 37 All these results indicated that AuNPs, especially 45-nm AuNPs, could enhance osteogenic differentiation and matrix mineralization. However, it cannot be denied that there are differences between ectopic and orthotopic models, and further well-designed experiments in alveolar bone-defect models are needed to verify the osteogenic effects of AuNPs on PDLSC sheets.…”
Section: Dovepressmentioning
confidence: 91%
“…COL1 is the most abundant protein in the ECM and acts as a scaffold for anchoring and distributing cells. 37 OPN is a major regulator of ECM mineralization and bone formation. 37 COL1 and OPN, these two ECM proteins fulfill the bone formation.…”
mentioning
confidence: 99%
“…Collagen is the most studied natural polymer for bone tissue engineering scaffolds, as this biopolymer integrates about 90 wt.% of natural bone ECM proteins [ 73 ]. Collagen can actively facilitate the osteogenic process of bone progenitor cells through a series of alpha–beta integrin receptor interactions and, as a result, can promote bone mineralization and cell growth [ 50 ].…”
Section: Polymer Scaffolds For Gf Deliverymentioning
confidence: 99%
“…Biglycan (Bgn) is a class I small leucine-rich proteoglycan (SLRP) that is expressed during cell proliferation and mineralization. By regulating TGF- β , Bgn plays an important role in survival as well as in the growth of BMSCs [ 67 ]. It was shown that knockout (KO) of miR-185 could increase the osteogenesis in primary osteoblasts collected from miR-185-KO mice as well as improved bone volume in KO mice.…”
Section: Mirnas Involved In Bmsc Regulationmentioning
confidence: 99%